Natural products chemistry : sources, separations and structures - Cooper, Raymond (CRC Press, 2015)
"Compounds isolated from nature have long been known to possess biological profiles and pharmaceutical potential far greater than anything made by man. However, they are notoriously cumbersome to isolate and challenging to synthesize, and the path of natural products to viable drugs is an arduous journey. This book presents a practical guide to gathering, isolating, and discovering new pharmaceuticals from nature. It emphasizes the challenges and advantages of products acquired from nature over traditional compounds such as those arising from combinatorial chemistry"--